Process Mining Pada Proses Pengadaan Barang dan Jasa Dengan Menggunakan Algoritma Heuristic Miner - Sabila Azka; Angelina Prima Kurniawati (eProceedings of Engineering, 2015)
Process mining is a technique used to help solve the existing problems in the process. An educational institution has definitely Procurement process. Evaluation of business processes in the Procurement of Goods and Services using process mining techniques are expected to find information about the location of the fault of the business process flow and provide suggestions for improvement system model Procurement processes that already exist to improve the performance of the business process. This study uses data from the event log Procurement Logistics Unit Telkom Engineering School as input during the process mining techniques. Results of this research is a picture of the new process models with flow changes in the activity of 'application for the specification of goods and services' that can be done without going through the activity of 'Identifying the needs of the goods required by the Faculty' and 'Establish the goods and services that will be submitted to the procurement of' first first, and the suggestion of time to carry out each activity. Key : Process mining, Event log, Procurement, Heuristics Miner